2013
DOI: 10.1371/journal.pone.0059016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparative Profiling of MicroRNAs in a Sexual Dimorphism Insect, Eupolyphaga sinensis Walker

Abstract: BackgroundMicroRNAs are now recognized as key post-transcriptional regulators in animal ontogenesis and phenotypic diversity. Eupolyphaga sinensis Walker (Blattaria) is a sexually dimorphic insect, which is also an important source of material used in traditional Chinese medicine. The male E. sinensis have shorter lifecycles and go through fewer instars than the female. Furthermore, the males have forewings, while the females are totally wingless.ResultsWe used the Illumina/Solexa deep sequencing technology to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 51 publications
1
27
0
2
Order By: Relevance
“…Another miRNA cluster that showed strong expression enriched in the embryonic stage is the miR-309/2944a/2944b/286 cluster, which contains miRNAs that are conserved in metazoan or insect species (Table S1 and S2). The expression patterns we observed in two mosquitos are consistent with those in flies (Leaman et al, 2005; Ninova et al, 2014), beetles (Marco et al, 2010), and moths (Wu et al, 2013). The miR-309 cluster has been shown to play roles in the degradation of maternal transcripts during maternal zygotic transition (MZT) in Drosophila (Bushati et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Another miRNA cluster that showed strong expression enriched in the embryonic stage is the miR-309/2944a/2944b/286 cluster, which contains miRNAs that are conserved in metazoan or insect species (Table S1 and S2). The expression patterns we observed in two mosquitos are consistent with those in flies (Leaman et al, 2005; Ninova et al, 2014), beetles (Marco et al, 2010), and moths (Wu et al, 2013). The miR-309 cluster has been shown to play roles in the degradation of maternal transcripts during maternal zygotic transition (MZT) in Drosophila (Bushati et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…MicroRNAs are known from more than 25 insect species, (Stark et al., 2007). Several miRNAs have been reported from various orders of insects such as Diptera, Hymenoptera, Coleoptera, Orthoptera, Lepidoptera, Hemiptera, Homoptera (Wu et al., 2013), and Thysanoptera (Rebijith, Asokan, Hande, & Krishna Kumar, 2016). This study reports the complete miRNA profile from onion thrips, Thrips tabaci .…”
Section: Discussionmentioning
confidence: 99%
“…Our homology and phylogeny analysis revealed that insect miRNAs are well‐conserved, despite considerable diversity in the genome (Figure 4a–d). MiRNA*s are not easily detectable as it degrades soon after being exported to the cytosol (Wu et al., 2013). However, our results indicated the presence of several miRNA*s (Tables 5 and 6) that matched to the same precursor sequences with their mismatched complementary mature miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations